1992
DOI: 10.1093/infdis/166.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin Skin Test Reactivity among Adults Infected with Human Immunodeficiency Virus

Abstract: Infection with the human immunodeficiency virus type 1 (HIV-1) results in decreased cell-mediated immunity, which includes decreased delayed hypersensitivity to skin test antigens. HIV-1 seropositivity and skin test reactivity to purified protein derivative (PPD) were determined among 2042 healthy Haitian adults with normal chest radiographs. Among HIV-1-seropositive individuals, 52.3% (146/279) had PPD reactions greater than or equal to 10 mm compared with 67.2% (1184/1763) of the seronegative adults (P less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2
5

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 6 publications
2
13
2
5
Order By: Relevance
“…Despite the effect of HIV on TST conversion, reactivity, and anergy (7,18), the observed reactivity among HIV-positive persons (40.5%) was still lower than those in the United States (52.3%), Haiti (65%), and Uganda (73.8%) (17,18,24). This could partially be explained by the presence of lower absolute CD4 ϩ T-cell counts in Ethiopians (33).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effect of HIV on TST conversion, reactivity, and anergy (7,18), the observed reactivity among HIV-positive persons (40.5%) was still lower than those in the United States (52.3%), Haiti (65%), and Uganda (73.8%) (17,18,24). This could partially be explained by the presence of lower absolute CD4 ϩ T-cell counts in Ethiopians (33).…”
Section: Discussionmentioning
confidence: 99%
“…Myer et al [19] reported a reduction in the DTH reaction in sheep infected with MVV, which, however, was not confirmed in a second series of experiments [16]. The finding of a reduction is analagous to the reduction of DTH skin reactions in the later stages of HIV infection [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when the serum test was used to identify individuals with M. tuberculosis infection in a group of HIV-infected persons as a model of deficient cellmediated immunity [17], the western blot showed a significant degree of concordance with the PPD skin test scored using 5 mm induration as the threshold, suggesting that this test may attain the same sensitivity as the skin test when it is used in its most sensitive mode.…”
Section: Discussionmentioning
confidence: 99%